Essential amino acid formulations to prevent mitochondrial dysfunction and oxidative stress. Issue 1 (January 2021) - Ruocco, Chiara; Segala, Agnese; Valerio, Alessandra; Nisoli, Enzo
Abstract : Purpose of review: Both restriction and supplementation of specific amino acids or branched-chain amino acids (BCAAs) are described to improve metabolic homeostasis, energy balance, and health span. This review will discuss the recent findings of the role of amino acid supplements in the regulation of mitochondrial health. Recent findings: A mixture of essential amino acids (EAAs), BCAA enriched mixture, was found to extend healthy life span in elderly mice and prevent multiple diseases associated with an energy deficit, similarly to caloric restriction or fasting-mimicking diets. A growing body of evidence highlights mitochondria as the central target of this supplement: it promotes mitochondrial biogenesis and the activation of antioxidant defence systems in different physiological (e.g., exercise or ageing) or pathological conditions (e.g., sarcopenia, muscular dystrophy, liver steatosis, or impaired cognition). Based on these results, new formulas have been created enriched with Krebs cycle substrates, behaving more efficiently than BCAA enriched mixture. Summary: EAA-BCAA balanced supplements might be valuable not only for healthy individuals undergoing to energy deficit (e.g., athletes) during strenuous exercise or training but also against diseases characterized by a dysregulated catabolic state or mitochondrial dysfunction, such as age-related disorders. The associated mechanistic processes should be identified as potential pharmacological targets.